Assessment of thermal energy storage integrated solar thermal collector system: a review - O. Afolabia, Lukmon; M. A. Elfaghia, Abdulhafid; Didane, Djamal Hissein; Ismail, Al Emran; Mat Isa, Norasikin (Penerbit UTHM, 2020)
Renewable solar energy is clean, abundant and globally available although intermittent in nature, thus requires storage ability whereby the solar radiation can be utilized and store simultaneously, the excess reuse during cloudy weathers and night time when there is no solar radiation. Continuous investigations by many researchers have shown that the integration of thermal energy storage (TES) to solar collector could improve the system performance and extend their utilization beyond solar radiation hours. Several studies utilizing different energy storage materials such as phase change materials (PCM), nanomaterials, PCM nanomaterials and hybrid PCM materials have reported improved heat transfer mechanism in solar thermal collectors. However, the demerits on weight, size and space increment, leakages and poor heat transfer mechanism caused by the PCM-TES incorporation with solar thermal collectors still persists despite the several research attempts on development of new smart PCM-TES materials and their incorporation. Thus far, the current mini-review paper attempts to bridge the literature gaps on past and recent PCM-TES integration techniques used for solar thermal collector systems. In addition, the performance analysis of existing designs, material fabrications and suggested improvement are discussed in this paper.